Water pollution and its impact on environment of society - Thyagaraju, N. (International research journal of management, IT and social sciences, 2016)
The present seminar paper mainly highlights the concept of water pollution, causes of water pollution, Its Effects, Elements of pollutants, Methods used to prevent the water pollution in the environment and the mandatory initiatives taken by the concerned authorities for prevention of water pollution. Water is essential for the survival of all living organisms on the earth. Thus for human beings and plants to survive on land, water should be easily accessible. The term “Pollution” generally refers to the addition of any foreign body either living or non – living or deletion of anything that naturally exists. The basic Sources of Water pollution causes due to Culmination into lakes, rivers, ponds, seas, oceans etc. Domestic drainage and sanitary waste, Industrial drainage and sewage, Industrial waste from factories, Dumping of domestic garbage, Immersion of Idols made of plaster of Paris, Excess use of Insecticides, pesticides, fungicides, Chemical fertilizers, Soil erosion during heavy rains and floods, Natural disasters, tsunami etc. General pollutants which are also caused for water pollution which include Organic, Inorganic, and Biological entities, Insecticides, Pesticides, Disinfectants, Detergents, Industrial Solvents, Acids, Ammonia fertilizers, heavy metals, Harmful bacteria, Virus, Micro-Organisms and worms, Toxic chemicals. Agricultural lands become infertile and thereby production also drops, Spread of epidemic diseases like Cholera, Dysentery, Typhoid, Diarrhea, Hepatitis, Jaundice etc. The basic responsibility of the Government, NGOs, National Pioneer scientific Research Institutions may conduct research oriented programs on control of water pollution by creating awareness among the public through mass media and Environmental Education on recycling units, and water treatment plants must be established both at domestic levels and Industry levels, Every citizen must feel responsible to control water pollution.